General Design and Layout of Datengxia Hydropower Station - ZHANG Xiao; YIN Shaoqing (Renmin Zhujiang)
Datengxia hydropower station is a riverbed power station with a low water head and large flow.It is installed with eight 200 MW axial-flow paddle turbine generating sets,with an average annual generating capacity of 6.055 billion kW·h,which makes early and remarkable economic benefits of generating sets possible.The buildings in the station mainly include the main engine room,installation room,outgoing line yard,sand retaining barrier,and drift retaining row.In combination with the construction diversion,the station adopts a left-and-right bank layout scheme and employs measures to optimize the prestressed reinforced concrete spiral case and layers and blocks in structural design,so as to minimize the project's total construction period and ensure the earliest power generation of the first set.The layout scheme and the optimal design of the station can provide a reference for other similar engineering designs.